The Moderating Effect of Transformational Leadership Style on Patient Safety Culture at Bhayangkara Hospital, Indonesia - Syah, Irwan; Jak, Yanuar; Sulistyowati, Yeny; Syafira Putri, Alsa; Rahmi, Dian (Universitas Muhammadiyah Yogyakarta, 2026)
Patient safety remains an important issue in health services and a global concern; it is crucial to ensure its implementation. This study aims to analyze the moderating effect of the transformational leadership style on workload, motivation, knowledge, and attitudes towards patient safety culture at Bhayangkara Polri Hospital. The research team used quantitative methods with an explanatory research approach. The sampling technique used was Slovin sampling, involving 117 nurse participants. The analysis technique uses partial least squares. Transformational leadership style variables cannot moderate workload, motivation, attitude, and knowledge of patient safety culture. The novelty of this research is that the researcher found that, in a specific context, Bhayangkara Depok Hospital still uses a command leadership style because its work culture is still influenced by that of the Indonesian National Police Institution (Polri). Hospital management regulations are still controlled by a higher-level organizational unit, in this case, the u.o Polri. The implementation of a highly complex patient safety culture is often influenced by numerous factors (exogenous variables). These include unique system characteristics, organizational business processes, and the individual behavior of Polri members assigned to Bhayangkara Brimob Depok Hospital.